A study of tourist’s motivation, intention and willingness to pay premium for ecotourism. - Costa, Juao; Lopes, Odilia Maria Honorina (Turizam, 2023)
The tourism business has grown dramatically in recent years. The tourist industry contributes significantly to a country's economic development. Goa, India's smallest state, is a popular tourist destination that draws visitors from all over the world. The sun and sand of Goa are well-known. It is surrounded by natural beauty and includes a variety of heritage sites, churches museums and temples. Goa is promoted internationally as a beach tourism resort that has reached its peak. As a result, there is a need to promote additional tourism options. The current research focuses on Goa's ecotourism. An attempt is made to identify latent motivational factors. Latent motivational factors were identified and categorised. This demonstrates that demographic considerations have no bearing on tourists' desire to participate in ecotourism. Tourists' willingness to spend more for ecotourism is also unaffected by demographic factors.